اشكالية حصانة القرارات الإدارية دراسة مقارنة - الحسين محمد; حبيب دانيال (Latakia University Journal - Economic and Legal Sciences Series, 2019)
Some constitutions and sometimes some laws protect certain administrative decisions from appeal, making them irrevocable. These decisions differ from acts of sovereignty in several respects, but they are similar insofar as they constitute a violation of the principle of the right to litigate. Of the acts of sovereignty, the second is relatively specific, while the first has no specific standard. The legislator can decide to fortify some administrative decisions regardless of their nature, while the acts of sovereignty may find some political or historical justification, but legislative fortification is not His justification. Therefore, this approach of some legislators makes the administration infallible and cannot interfere with its actions and decisions, which constitutes a wide violation of the principle of the right of litigation and the rule of law. تنص بعض الدساتير وأحیاناً بعض القوانين على تحصین بعض القرارات الإدارية من الطعن، بحیث تجعلها باتة لا طعن فیها ، وهذه القرارات تختلف عن أعمال السیادة في عدة نواحي، إلا إنهما یتشابهان من حیث كونهما یشكلان خرقاً لمبدأ حق التقاضي المقدس، بل إن المجموعة الأولى تعد أخطر من أعمال السیادة، كون الثانیة محددة نسبیاً، في حین أن الأولى لیس لها معیار محدد، إذ یمكن للمشرع أن یقرر تحصین بعض القرارات الإدارية وبغض النظر عن طبیعتها ، في حين إن أعمال السیادة قد نجد لها بعض التبریرات السیاسیة أو التاریخیة ، لكن التحصین التشریعي لیس له ما یبرره. وعلیه فإن هذا التوجه لدى بعض المشرعین یجعل من الإدارة معصومة الخطأ، ولا یمكن التعقیب على أعمالها و قراراتها، وهذا یشكل خرقاً واسعاً لمبدأ حق التقاضي ولدولة القانون.